Adsorption of polymer-surfactant mixtures at the oil-water interface - Tucker, Ian M (Langmuir : the ACS journal of surfaces and colloids, 2012)
Small-angle neutron scattering, zeta potential measurements, and dynamic light scattering have been used to investigate the adsorption of polymer-surfactant mixtures at the oil-water interface. The water-hexadecane interface investigated was in the form of small oil-in-water emulsion droplets stabilized by the anionic surfactant sodium dodecyl sulfate, SDS. The impact of the addition of two different cationic polymers, poly(ethyleneimine), PEI, and poly(dimethyldiallylammonium chloride), polydmdaac, on the SDS adsorption at the oil-water interface was studied. For both polymers, the addition of the polymer enhances the SDS adsorption at low SDS concentrations at the oil-water interface due to a strong surface polyelectrolyte-surfactant interaction and complexation, but the effects are not as pronounced as at the air-water interface. For PEI/SDS, the adsorption was largely independent of solution pH and increasing PEI concentration. In marked contrast to the adsorption at the air-water interface, only monolayer adsorption and no multilayer adsorption was observed. For the SDS-polydmdaac mixture, the enhanced SDS adsorption was in the form of a monolayer, and the adsorption increased with increasing polymer concentration. The strong SDS/polydmdaac surface interaction resulted in regions of emulsion instability. The zeta potential measurements showed that the combination of SDS and polydmdaac at the interface resulted in charge reversal at the interface. This correlates with the regions of emulsion stability at both high and low polymer concentrations, such that the instabilities arise in the regions of low or zero surface charge. The results presented and their interpretation represent a development in the understanding of polymer-surfactant adsorption at the oil-water interface